Rehabilitation of Fly Ash Dump Yard Shaktinagar Super Thermal Power Station Through Afforestation - Lal, Shyam (Indian Forester, 1996)
The results of rehabilitation of fly ash dump through afforestation by planting leguminous species arc presented in this paper.